Reply to ?Comment on `Size-dependent scaling of perpendicular exchange bias in magnetic nanostructures??? - VAN DIJKEN, SEBASTIAN; COEY, JOHN MICHAEL DAVID (American Physical Society, 2008)
Our observation of size-dependent scaling effects at room temperature in exchange-biased multilayers grown onto arrays of polystyrene nanospheres Phys. Rev. B 75, 012413 2007 does not conflict with the observation by Baltz et al. of a crossover to thermally activated spin reversal in the antiferromagnetic layer upon patterning Phys. Rev. Lett. 94, 117201 2005 . We mention a few dissimilarities between the two systems that might account for a different behavior at room temperature.
PUBLISHED
Keywords: Physics